Higher education funding reforms in England: The distributional effects and the shifting balance of costs - Lorraine Dearden; Emla Fitzsimons; Alissa Goodman; Greg Kaplan (Institute for Fiscal Studies (IFS), 2007)
This paper undertakes a quantitative analysis of substantial reforms to the system of higher education (HE) finance in England, first announced in 2004 and revised in 2007. The reforms introduced deferred fees for HE, payable by graduates through the tax system via income-contingent repayments on loans subsidised by the government. The paper uses lifetime earnings simulated by the authors to consider the likely distributional consequences of the reforms for graduates. It also considers the costs of the reforms for taxpayers, and how the reforms are likely to shift the balance of funding for HE between the public and private sectors.
Keywords: 330; Bildungsfinanzierung; Bildungsreform; Verteilungswirkung; Großbritannien